"Not an Ounce of Hollywood Bullshit": A Narrative Analysis of News Media Coverage of Spotlight's Oscar Win. (April 2020) - Bishop, Ronald
A narrative analysis was conducted of news media coverage of the Academy Award-winning movie Spotlight from January 1, 2015, until June 1, 2016, with a focus on how journalists, film critics, and commentators invoked the history of investigative reporting—and of investigative reporting on film—in evaluating Spotlight and the significance of the journalism-related issues it raised. Even as the narrative asks the reader to revisit the "heroic journalist" myth, its elements mitigate against endorsement: the field's financial distress, the focus on "grunt work, " the desire of the film's creators to honor journalism's past, the impression that journalists had been cordoned off somewhere until the film reintroduced us to them, and the Spotlight team begrudgingly accepting Hollywood's demands—even the repeated comparisons to All the President's Men —coalesce to negate the film's potential to remind us of the need for aggressive, uncompromising investigative reporting and to affirm the myth of the dogged investigative journalist.